BIOSECURITY STUDY TEXTILE PRODUCTS (CAHIERS MAGELLANES-NS, 2024)
The article describes :  the purpose of antibacterial fabrics, methods of antibacterial treatment of textile materials with biocidal preparations. The concepts between the following three types of materials are given: antibacterial, bactericidal, bacteriostatic, for a clear definition of the differences between them. The necessity of developing antibacterial preparations without using harmful chemical reagents has been substantiated. In the experimental part, the possibility of impregnating tik-sarzha tissue with biopreparations based on nitrogen-containing heterocyclic compounds and 4% solution of microelements (combinations of zinc, copper, iron) in the chelate state was investigated.Determination of antimicrobial action of tissue samples with different impregnation was  carried  out  by diffusion method in dense agar nutrient medium against some species of bacteria. When antibacterial treatment of investigated tissue samples during the experiment optimal variants of technological modes were obtained. Results of the study made it possible to conclude that antimicrobial activity against all test strains was observed in the samples tested against pathogenic and conditionally pathogenic test strains. The samples tested have antimicrobial activity against the test strains and relatively high antimicrobial activity against the test strain Candida albicans (20- 26 mm). In order to optimize the technological processes of antibacterial treatment of tissues, it is necessary to expand the range of treated biocompositions and continue research.